Handbook of Occupational Safety and Health as a Guiding Supplement for Occupational Safety and Health in Chemical Laboratory - Sudiana, Ketut (International Journal of Natural Science and Engineering, 2022)
Chemical education laboratories have a higher risk of work accidents than laboratories for industrial activities. Many work accidents occur in chemical laboratories. Two factors that cause work accidents are unsafe behavior and unsafe conditions. Occupational safety and health in the laboratory are crucial to creating a comfortable, safe work environment to prevent or minimize workplace accidents. This study aims to produce a handbook of occupational safety and health in chemical laboratories as a guiding supplement for chemistry practicum to create occupational safety and health in chemical laboratories. This research is a research and development (r&d) with a 4-d development model consisting of 4 main stages: define, design, develop and disseminate. Research is limited to the development stage, which ends with a practicality test. Based on expert judgment, it was found that the occupational safety and health handbook in the chemical laboratory are very valid in terms of content (3.9), language (4.0), and media (4.0), from a maximum score of 4. From the readability test, all respondents obtained students understand the content or information presented in the chemical laboratory’s occupational health and safety handbook. Furthermore, through the practicality test, it was obtained that lecturers, laboratory assistants, and students gave an assessment that the occupational safety and health handbook in the chemical laboratory each scored 4.0 and 3.9, which means it is very practical. This research concludes that the chemical laboratory’s occupational safety and health guidebook as a guiding supplement for chemistry practicum is valid to be implemented from the aspect of content, language, media, and readability and is very practical in its use.